Implementation of the Rain Hadith Interpretation Methodology in Strengthening the Character of Independence and Responsibility of 5-6 Year Old Children at Al Muhajirin Tempuran Preschool - Nurhayati Nurhayati; Sofa Sofa; Marwah Marwah; Nunung Nurhayati; Omah Rohimah (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2026)
Early Childhood Education (PAUD) plays a crucial role in shaping children's basic character, particularly independence and responsibility as the foundation of their future personality. From an Islamic educational perspective, character formation is not merely theoretical but must be instilled through habits and role models from an early age. The Ra'in Hadith, which emphasizes that every individual is a leader and will be held accountable for their responsibilities, serves as a relevant normative foundation for strengthening children's character. However, the reality on the ground shows that some children aged 5-6 still rely on teachers to complete simple tasks, and character education has not been optimally integrated with Islamic values. This study aims to analyze the implementation of the Ra'in Hadith interpretation methodology through a thematic and contextual approach to strengthening the character of independence and responsibility in 5-6 year old children. The study used a descriptive approach with data collection techniques including observation, interviews, and documentation. The research subjects included the principal, group B teachers, and students at the Al-Muhajirin Early Childhood Education (PAUD) in Tempuran District. The study was conducted over eight weeks using a saturated sampling technique. The results showed that in the initial stages, children's independent and responsible character traits still needed strengthening. Children tended to rely on teachers, were less consistent in following rules, and had not yet demonstrated a full awareness of their responsibilities. After implementing the thematic and contextual interpretation of the Ra'in hadith methodology, positive changes occurred in children's behavior. Children began to be able to complete tasks independently, tidy up play equipment, and demonstrate concern for the classroom environment through habits linked to the value of trust. The study's conclusions confirm that integrating the values ​​of the Ra'in hadith through a thematic and contextual approach, accompanied by teacher role models and consistent habits, is effective in strengthening the independent and responsible character traits of early childhood children in PAUD institutions.